Role of lactoferrin in the treatment of E. coli-induced bovine mastitis - Mohamed Ibrahim Mostafa; Saber Ali Saad; Asmaa Elsayed Mohammed; Elsaid Mohamed Mohamed Saafan; Amal Mohamed El-Sayed (Open Veterinary Journal)
Background: Bovine mastitis is a costly disease in the dairy industry. It is associated with reduced milk production and changes in milk composition and quality. E. coli is the most important pathogen causing bovine mastitis.